AI-Mediated Visual Narratives and the Construction of South Korea's Cultural Identity in K-pop Music Videos - Meilia Afina Khusnawati; Maya Diah Nirwana (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines how artificial intelligence (AI) mediated visual narratives in aespa’s music videos construct and circulate South Korean cultural identity within the global digital sphere. Grounded in Stuart Hall’s theory of representation, the research adopts an interpretive qualitative approach using an intrinsic case study design. Two official music videos, Next Level (2021) and Savage (2021), are analyzed as cultural texts rather than entertainment products. Through systematic visual analysis, the study investigates how AI-driven aesthetics such as digital avatars, metaverse environments, glitch effects, and posthuman imagery interact with traditional Korean cultural symbols, including hanbok-inspired costumes, mythological references, architectural motifs, choreography, and linguistic hybridity (Konglish). The findings reveal that AI functions not as a neutral production tool but as a representational system that actively articulates meaning. By strategically combining tradition and futurism, aespa’s visual narratives produce a hybrid form of “Koreanness” that is simultaneously locally rooted and globally legible. This hybrid identity is encoded by the entertainment industry through AI-mediated visuals and decoded by global audiences within digital platforms, enabling the effective circulation of South Korean cultural identity without erasing cultural specificity. The study contributes to digital cultural studies by demonstrating that AI operates as a cultural agent within popular media, shaping how national identity is negotiated, commodified, and reimagined in contemporary global culture.